Hemodynamic Changes During Heart Displacement in Aorta No-Touch Off-Pump Coronary Artery Bypass Surgery: A Pilot Study - Carvalho,Alexandre R. (2018)
Abstract Objective: To evaluate the sequential changes of hemodynamic and metabolic parameters in patients who underwent aorta no-touch off-pump coronary artery bypass surgery (OPCAB). Methods: Prospective study involving twenty-seven consecutive patients who underwent aorta no-touch OPCAB. The FloTrac/PreSep/Vigileo™ system (Edwards Lifesciences) was used to continuously record heart rate (HR), mean arterial blood pressure (MABP), central venous pressure (CVP), continuous cardiac index (FCI), stroke volume (SV), stroke volume variation (SVV), and central venous oxygen saturation (ScvO2). The parameters were assessed 5 min before, during and 5 min after each anastomosis (left anterior descending [LAD], posterior descending [PD], obtuse marginal [OM] and diagonal [Dg]). Postoperative lactate was also evaluated. Results: There was no significant change in HR and MABP for all anastomoses, except for MABP during PD grafting (-10.1±2.7 mmHg, P=0.03). There was a significant decrease in ScvO2 only during PD and OM anastomoses (-9.4±0.4, P=0.03; -4.4±0.4, P=0.02; respectively). CVP drop after PD manipulation was strongly associated with a higher lactate during the first hours after surgery (r=-0.82; P=0.001). These hemodynamic changes were transient and entirely recovered after the heart was returned to its anatomical position. No significant differences were observed in FCI, SVV, or the systemic vascular resistance index (SVRI) during all anastomoses, except for a drop in SVRI during PD grafting (-8.03±2.3, P=0.007). SV tended to decrease during the procedure in all territories, but with statistically significant drop only in PD and OM grafting (-10.4±1.2, P=0.02; -13.6±5.1, P=0.007; respectively). Conclusion: Heart displacement for performing aorta no-touch OPCAB is well tolerated, with transient and endurable hemodynamic variations.